The Strategy of Developing Public Speaking Skills Among Students Through Debate in Arabic Based on the Qatar Debate Methodology - Abdullah, Ahmad Hafidz; Muhyidin, Muhyidin; Amalia, Nabila Nailil; Mayasari, Utari Dwi (Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2024)
This study explores the application of the Qatar Debate methodology to enhance Arabic students' public speaking skills through debate simulations. The study aimed to improve students' verbal fluency, confidence, and critical thinking by encouraging them to analyze, formulate arguments, and actively engage in Arabic discourse. The research was conducted at the Key to Islamic Sciences University in Lumajang, integrating formal instruction in academic debate. Fifteen students participated in this study, using a qualitative descriptive approach. Data were collected through observation, interviews, and recordings, with analysis following the Miles and Huberman model. The findings indicate that debate simulations, based on the Qatar Debate methodology, significantly enhance students' Arabic public speaking and critical thinking abilities..